Secure communication for autonomous vehicles - Thanh, Vu Duy (2017)
The growth of autonomous vehicles in recent years has brought more attentions to the development ofa Vehicular Ad-hoc Network (VANET) to facilitate the driving ability of vehicles. It is important, especially for the protection of driverless cars from which the navigating decisions are made automatically, to ensure the security of the network communication. In this project, the security protocols are studied to propose secure authentication methods for communication in VANETs. The security protocols are developed based on an existing Public Key Infrastructure (PKI) used to provide security services in VANETs. There are three proposed protocols in this project for device authentication in three main types of network communication which are certificate establishment, message verification and confidential data transmission. The designed protocols are successfully verified of logic correctness and demonstrate lower communication overheads in comparison with the existing related schemes.